Optimizing cold chain logistics for bio fortified crops - Herawati Susi; Dwikora Simanjuntak Pargaulan; Fahcruddin Imam; Siahaan Rosna Yuherlian; Watty Sihombing Derma; Alamsyah Jaya; Ari Wibowo Titis (BIO Web of Conferences)
This research investigates the optimization of cold chain logistics for biofortified crops in Southeast Asia, focusing on infrastructure, regulatory frameworks, stakeholder collaboration, and environmental impact. Through a multidisciplinary approach, including qualitative and quantitative methods, key indicators and parameters were analysed to assess the current state and identify opportunities for improvement. Findings reveal strengths in storage facilities, refrigeration technologies, and government regulations, yet challenges persist in transportation efficiency, industry standards, and waste management. Collaboration among stakeholders, particularly in government partnerships and private sector engagement, is essential for enhancing cold chain resilience and sustainability. Addressing environmental impacts, such as energy efficiency and waste reduction, is crucial for promoting eco-friendly practices and mitigating climate risks. The research underscores the importance of strategic investments, policy reforms, and collaborative initiatives to ensure the efficient and sustainable delivery of biofortified crops, thereby contributing to food security, nutrition, and environmental conservation in Southeast Asia.